Recovery algorithm for multicast tree - Sadagopan Sridharan (2008)
Ad hoc network enables communication between nodes without any additional infrastructure. Our proposed algorithm first identifies the recovery region which limits the recovery actions to the region around the location of failure by identifying the set of nodes to be included in the recovery process.